Effect of cognitive-behavioral therapy on fatigue in cancer patients: a systematic review and meta-analysis - Hosseini Koukamari, Parisa; Karimy, Mahmood; Ghaffari, Mohtasham; Milajerdi, Alireza (Frontiers in Psychology, 2025)
BackgroundFatigue is a prevalent issue among cancer patients. Cognitive behavioral therapy (CBT) is an individualized intervention that empowers patients and caregivers to actively participate in the treatment process. A recent systematic review and meta-analysis examined the impact of CBT on fatigue in cancer patients.MethodsArticles published up to April 2023 were systematically searched in Scopus, PubMed, and the Web of Science using relevant keywords. All randomized clinical trials (RCTs) investigating the effects of CBT on fatigue in cancer patients were included. Statistical analyses were conducted using Stata version 14, with a significance level set at a p-value of <0.05.ResultsThe current systematic review and meta-analysis encompasses 10 RCTs. CBT demonstrated a significant reduction in fatigue scores among cancer patients [standardized mean difference (WMD): −2.50; 95%CI: −3.43, −1.56; I2 = 95.8%, p < 0.001]. This effect was consistent across all subgroup analyses.ConclusionThis study underscores the significant impact of CBT on fatigue in cancer patients. Further randomized clinical trials focusing on various cancer types are warranted to validate and build upon these findings.